DNA, Technology, and Florida Strawberries - Seonghee Lee; Young-Hee Noh; Sujeet Verma; Vance M. Whitaker (EDIS, 2016)
Are Florida strawberries genetically engineered? The answer is no. No genetically engineered strawberry has been commercialized anywhere in the world. The UF/IFAS strawberry breeding program has been developing strawberry varieties for nearly 70 years, but these varieties are developed using a conventional breeding process of crossing and selection. This 4-page fact sheet describes that process in greater detail. Written by Seonghee Lee, Young-Hee Noh, Sujeet Verma, and Vance M. Whitaker, and published by the Horticultural Sciences Department, November 2016.